Hodnocení finanční situace podniku a návrhy na její zlepšení - Belan, Vojtěch (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Bakalářská práce je zaměřena na hodnocení finanční situace podniku a předkládá návrhy na její zlepšení pomocí finanční analýzy. Práce je rozdělena na teoretickou a praktickou část. Teoretická část slouží k objasnění základních pojmů, které jsou dále použity v praktické části, která je věnována finanční analýze společnosti Makita, spol. s r.o. v období 2014–2019. Na základě hodnot, získaných touto analýzou, jsou předloženy návrhy na zlepšení situace.

This Bachelor's Thesis is focused on the evaluation of a company's financial situation and brings suggestions on how to improve it using methods of financial analysis. The Thesis is divided into theoretical and practical part. The theoretical part explains basic concepts that are used in the practical part, where the practical part is focused on the financial analysis of a company Makita, spol. s r.o., for the period of 2014–2019. Suggestions for improvements are made based on the outcomes of the analysis.
Evaluation of the Financial Situation of a Company and Proposals for its Improvement
Keywords: Finanční analýza; SWOT analýza; likvidita; rentabilita; zadluženost; cash flow; index INO5; Financial analysis; SWOT analysis; liquidity; profitability; indebtedness; cashflow; index IN05